PENGEMBANGAN MEDIA PEMBELAJARAN DIORASMART PADA MATA PELAJARAN GEOGRAFI DI SMA NEGERI 13 MAKASSAR - Qadri, Muh. Nuzul; Febriati, Farida; Mawarni, Sella (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Geography learning, especially on volcanism material, requires media that can help students visualize abstract concepts more realistically. However, limited time and learning media used by teachers only using maps, atlases, globes, and videos from Youtube make students tend to get bored in the learning process. Therefore, this study aims to develop Diorasmart learning media, a learning media that combines Android-based applications in the form of Smart Apps Creator (SAC) and 3-dimensional volcano dioramas. This study uses the ADDIE development model consisting of five stages: analysis, design, development, implementation, and evaluation. At the analysis stage, observations and needs questionnaires were conducted to determine students' difficulties in understanding volcanism material. At the design stage, the SAC application was designed with interactive animation features, educational videos, and quizzes, while the volcano diorama was developed to provide a real visual depiction. After going through the development stage, Diorasmart was tested for validity by material experts and media experts, and tested on students and teachers to measure its level of practicality and effectiveness. The results of the study indicate that Diorasmart has a high level of validity and is valid for use in geography learning. Teachers' and students' responses to this media are very positive, especially in terms of ease of use and visual appeal. In addition, student learning outcomes through pretest, posttest, and paired samples tests show that Diorasmart is effective in improving student understanding. Thus, Diorasmart can be an innovative solution in geography learning, especially in volcanism material, and has the potential to be further developed in other geography materials.